Kedudukan Al-Qur’an dalam Sumber Hukum Islam: Melacak Pemikiran Islam Melalui Kajian Ushul Fiqh - Ayu Karina; Dea Puspita; Uum Umaroh Husaeni; Hafidz Taqiyuddin (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study aims to examine the position of the Qur’an as a source of law in Islam with the ushul fiqh approach. The main focus of this study is the exploration of Islamic thought related to the development of Qur’anic law. The method used is a qualitative approach through library studies, where data is collected from primary and secondary sources. The results of the study indicate that the Qur’an has the highest authority in the Islamic legal system, is dynamic, and open to methodological interpretation. Thus. This study reveals that a contextual understanding of the texts of the Qur’an is very important to answer complex legal issues in the contemporary era.